ANALYSIS OF GRAMMATICAL ERROR IN DESCRIPTIVE WRITING AMONG STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF STKIP AGAMA HINDU SINGARAJA IN THE ACADEMIC YEAR OF 2020/2021 - Ni Wayan Monik Rismadewi (Daiwi Widya, 2021)
The present study aimed at: (1) investigating the types of grammatical errors committed by the second semester students of English Education Department of STKIP Agama Hindu Singaraja in writing descriptive text and (2) explaining the causes of grammatical errors committed by the second semester students of English Education Department of STKIP Agama Hindu Singaraja in writing descriptive text. The data were collected by using documentation, questionnaire and interview. The study was descriptive study. The instruments were writing instruction, self assessment, questionnaire, interview guide and tape recorder. The study revealed that there were four kinds of errors found in their writing text, such as: verb errors, preposition errors, article errors and pronoun errors. Total of errors that the students committed was 538 errors. The most frequent errors were in the use of verb as many as 285 errors or 52.97%. There were 189 errors in the use of article or 35.13%. In the use of pronoun was found as many as 39 errors or 7.24%. Meanwhile, there were 25 errors in the use of preposition or 4.64%. There were four causes of errors committed by the students namely: the interference of the learners’ mother tongue, context of learning, overgeneralization, ignorance of rule restrictions. The result from interview showed that the students’ grammatical errors were mostly caused by intralingual factor which is grammar and structure.